Optimal space maneuvers in three dimensions - Schulz,Walkiria (2006)
The objective of this paper is to study the problem of orbital maneuvers for an artificial satellite moving in a Keplerian Force Field. Analytical equations are derived to solve this problem. Several cases are studied to validate the algorithm developed. The results show that the theory developed here are suitable for real simulations and mission analysis.